An analysis of recent policies for beef and milk - O'Connor, R. (Statistical and Social Inquiry Society of Ireland, 1970)
Special policies have to be introduced for agriculture in developed economies. It appears that if present policies are continued the expenditure will continue to grow in future years. Hence, a crucial matter for policy-makers is to consider if this rate of growth in expenditure is justified, taking accounts of the overall national economy and also if the present pattern of expenditure is suitable, or whether it should be altered in some way The larger question relating to the overall level of State aid is outside the scope of this paper, which is concerned specifically with policies for beef and milk. In order to consider the latter policies, however, we must outline some broad criteria governing State aid to agriculture generally
Read before the Society, 16 January, 1970
Keywords: Irish agriculture; Beef; Milk; Agriculture policy; 314.15